2020
DOI: 10.21203/rs.3.rs-92252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted suppression of microRNA-33 in lesional macrophages using pH low-insertion peptides (pHLIP) improves atherosclerotic plaque regression

Abstract: Hypoxia and tissue acidification occur in the macrophage-rich regions of advanced atherosclerotic lesions due to the higher oxygen demand of activated immune cells and insufficient oxygen supply. Our group and others originally identified microRNA-33 (miR-33) as critical regulator of cellular lipid homeostasis and lipoprotein metabolism controlling the development of atherosclerosis. Our prior work has demonstrated that pH Low-Insertion Peptides (pHLIP) can be used to direct miR-33 inhibitors to acidic microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, lipid‐laden macrophages within atherosclerotic plaques have also been shown to have low pH, suggesting that these same delivery systems may also be useful for targeted delivery of inhibitors of miR‐33 and other miRNA therapeutics for the treatment of atherosclerosis. Indeed, our recent work has demonstrated that pHLIP‐conjugated inhibitors of miR‐33 can effectively target miR‐33 in the macrophages that make up atherosclerotic plaques leading to stabilization of the lesions (preprint: Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lipid‐laden macrophages within atherosclerotic plaques have also been shown to have low pH, suggesting that these same delivery systems may also be useful for targeted delivery of inhibitors of miR‐33 and other miRNA therapeutics for the treatment of atherosclerosis. Indeed, our recent work has demonstrated that pHLIP‐conjugated inhibitors of miR‐33 can effectively target miR‐33 in the macrophages that make up atherosclerotic plaques leading to stabilization of the lesions (preprint: Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%